Two antler crossbow nuts and some notes on the early development of the crossbow - MacGregor, Arthur (Proceedings of the Society of Antiquaries of Scotland, 1978)
Antler crossbow nuts from contexts of possible Early Christian and medieval date respectively from Buston Crannog and Urquhart Castle provide rare examples for the history of the crossbow in Britain. A R. See also 78/5590.